2021
DOI: 10.1111/zsc.12492
|View full text |Cite
|
Sign up to set email alerts
|

Genomic assessment of the Phyllodactylus tuberculosus complex (Reptilia: Phyllodactylidae) in America

Abstract: Leaf‐toed geckos (Phyllodactylus) exhibit much cryptic diversity, at least in North America. However, the origins of Central American taxa and their relationships with North American congeners remain unknown. The P. tuberculosus species complex is ideal for evolutionary and biogeographic studies because its geographic distribution extends from northern Mexico to Costa Rica. We analyse ~2,500 nuclear loci obtained by the GBS genomic technique to test hypotheses of genetic isolation among taxa and estimate times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…To identify the spatial distribution of reptile records in the study region, we projected all geo-referenced records onto our study area polygon using ArcGIS software, version 10.0 (ESRI 2010). To determine the distribution and taxonomically standardize the data set of species that inhabit the Selva Zoque and the other tropical regions, we consulted the specialized literature documenting taxonomic changes and descriptions of new species (Wüster et al 2005;Castoe et al 2009;Köhler 2010;Linkem et al 2011;Cadle and Savage 2012;Hedges and Conn 2012;Iverson et al 2013;Porras et al 2013;Köhler et al 2014;Ruane et al 2014;Blair et al 2015;Meza-Lázaro and Nieto-Montes de Oca 2015;Card et al 2016;Gray et al 2016;Köhler et al 2016;McCranie and Hedges 2016;Wallach 2016;Nieto-Montes de Oca et al 2017;Campbell et al 2018;Carbajal-Márquez et al 2020;Jadin et al 2020;McCranie et al 2020;Reyes-Velasco et al 2020;Ramírez-Reyes et al 2021). Using the compiled data, we defined four distribution categories: species distributed outside Mesoamerica as widely distributed species (WD), species restricted to Mesoamerica (MA), species restricted to northern Mesoamerica (MAMx), and species restricted to one of the eight regions considered.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…To identify the spatial distribution of reptile records in the study region, we projected all geo-referenced records onto our study area polygon using ArcGIS software, version 10.0 (ESRI 2010). To determine the distribution and taxonomically standardize the data set of species that inhabit the Selva Zoque and the other tropical regions, we consulted the specialized literature documenting taxonomic changes and descriptions of new species (Wüster et al 2005;Castoe et al 2009;Köhler 2010;Linkem et al 2011;Cadle and Savage 2012;Hedges and Conn 2012;Iverson et al 2013;Porras et al 2013;Köhler et al 2014;Ruane et al 2014;Blair et al 2015;Meza-Lázaro and Nieto-Montes de Oca 2015;Card et al 2016;Gray et al 2016;Köhler et al 2016;McCranie and Hedges 2016;Wallach 2016;Nieto-Montes de Oca et al 2017;Campbell et al 2018;Carbajal-Márquez et al 2020;Jadin et al 2020;McCranie et al 2020;Reyes-Velasco et al 2020;Ramírez-Reyes et al 2021). Using the compiled data, we defined four distribution categories: species distributed outside Mesoamerica as widely distributed species (WD), species restricted to Mesoamerica (MA), species restricted to northern Mesoamerica (MAMx), and species restricted to one of the eight regions considered.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…During these visits two amphibians were recorded, Eleutherodactylus pallidus Duellman, 1958 andSmilisca baudinii (Duméril &Bibron, 1841), and for the first time the snake Rhadinaea hesperia Bailey, 1940(Nolasco-Luna et al 2017. As a result of these explorations, specimens of Phyllodactylus were secured on Isla María Cleofas, and it was demonstrated that island populations were genetically isolated from mainland populations (Ramírez-Reyes et al 2021a, 2021b, which consequently lead to the description of a new species: P. cleofasensis (Ramírez-Reyes et al 2021a). Based on the information mentioned above, we provide an updated checklist of the amphibians and reptiles of Isla María Cleofas, including three new records, description of new species, and taxonomic changes.…”
Section: Introductionmentioning
confidence: 99%
“…P. magnus is a recently elevated species of the subspecies Phyllodactylus tuberculosus magnus (Ramírez-Reyes et al 2021). The known distribution for the species is in the states of Guerrero, Oaxaca and Chiapas along the Pacific coastal plain (Ramírez-Reyes et al 2021).…”
mentioning
confidence: 99%